Dispersing Pt and Pd atoms on Au nanoparticles deposited on n-GaN substrates for formic acid oxidation. Issue 112 (29th October 2015) - Qin, S.-J.; Zhao, Y.; Peng, F.; Chen, X.-Q.; Pan, G.-B.
Abstract : Au nanoparticles, with dispersed Pt and Pd atoms on them, supported on n-GaN substrates were prepared. The catalysts showed an enhanced performance for formic acid oxidation, and the mass activity reached 3.5 mA μgPtPd −1 . Abstract : Au nanoparticles, with an ultra low-loading of Pt and Pd atoms, supported on n-GaN were prepared using electrochemical atomic layer deposition and surface-limited redox replacement. The as-prepared electrocatalysts showed an enhanced performance for formic acid oxidation, and the mass activity reached 3.5 mA μgPtPd −1 . The active sites of the Pt Chem-O species were found to play a key role in formic acid oxidation.